2007
DOI: 10.2172/930881
|View full text |Cite
|
Sign up to set email alerts
|

Final Report - Assessment of Potential Phosphate Ion-Cementitious Materials Interactions

Abstract: The objectives of this limited study were to: (1) review the potential for degradation of cementitious materials due to exposure to high concentrations of phosphate ions; (2) provide an improved understanding of any significant factors that may lead to a requirement to establish exposure limits for concrete structures exposed to soils or ground waters containing high levels of phosphate ions; (3) recommend, as appropriate, whether a limitation on phosphate ion concentration in soils or ground water is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Those two processes, i.e., the adsorption of phosphates on cement grains and the formation of the HAP, were likely to contribute to the observed efficient crack closure of the samples in Exposure 2. In fact, both CSH as well as calcite present inside the crack were shown earlier to be efficient in the removal of phosphates from phosphate-contaminated solutions [41,42,43]. This could further support the hypothesis, assuming the formation of a calcium phosphate compound inside the crack.…”
Section: Resultssupporting
confidence: 53%
“…Those two processes, i.e., the adsorption of phosphates on cement grains and the formation of the HAP, were likely to contribute to the observed efficient crack closure of the samples in Exposure 2. In fact, both CSH as well as calcite present inside the crack were shown earlier to be efficient in the removal of phosphates from phosphate-contaminated solutions [41,42,43]. This could further support the hypothesis, assuming the formation of a calcium phosphate compound inside the crack.…”
Section: Resultssupporting
confidence: 53%
“…The concentration ranges in GiD‐powder and GiD‐concrete were found in the order nitrate > chloride > sulfate > phosphate. The level of anions concentration in GiD‐powder and GiD‐concrete is within an acceptable range when compared to SCTLs for residential and commercial zones . Hence, based on the presented results it can be concluded that GiD‐concrete at 20% addition of GiD‐powder is considered safe with respect to human health and has a negligible negative impact on the surrounding soil.…”
Section: Resultssupporting
confidence: 52%
“…46 Concrete exposed to a marine environment may deteriorate as a result of combined effects of chemical action of sea water constituents on cement hydration products, alkali-aggregate expansion if reactive aggregates are present, crystallization pressure of salts within concrete if one face of the structure is subject to wetting and others to drying conditions, frost action in cold climates, corrosion of embedded steel reinforcement, and physical erosion due to wave action or floating objects. 144 The data show that in an ordinary portland cement system the formation of calcium hydroxyapatite is capable of replacing free calcium hydroxide (Portlandite) and competes successfully for calcium in aluminosilicate matrices. In order to determine if this can lead to degradation of concrete through expansive reactions, a literature review and small-scale laboratory investigation was conducted.…”
Section: Acids and Basesmentioning
confidence: 98%
“…Results of the literature review indicated that no harmful interactions of phosphate and cementitious materials occur unless the phosphates are present in the form of phosphoric acid. 144 The laboratory study involved casting cement paste cubes and prisms that were cured in solutions of calcium hydroxide (control), magnesium phosphate, and sodium phosphate. Periodically specimens were removed from each of the curing solutions and measured, weighed, evaluated for compressive strength, and examined by x-ray diffraction or scanning-electron microscope methods.…”
Section: Acids and Basesmentioning
confidence: 99%